Wound care for a patient with diabetic foot of Wagner grade 3 (1例Wagner 3级糖尿病足患者的伤口护理) - XIAO Mengyun (肖孟云); GAN Lu (甘露); KONG Deming (孔德明); XIE Wei (谢薇); ZHANG Youqiong (张友琼); JIANG Yonghong (江永红); CHEN Maosong (陈茂松) (Association of Integrative Nursing, 2022)
This paper summarized the experience of wound care for a patient with diabetic foot of Wagner grade 3. Based on the clinical evaluation of illness condition and risk assessment, targeted nursing interventions on wound dressing, pain control, nutrition support and psychological care were carried out, in order to improve the recovery of diabetic foot ulcers. (本文总结1例Wagner 3级糖尿病足患者的伤口护理经验, 通过科学评估, 了解患者整体情况, 明确风险因素, 以此制定针对性的伤口换药、疼痛干预、营养支持以及心理干预方案, 帮助患者树立治疗信心, 促进患者伤口恢复。)